Time course of adiponectin and its relationship to psychological aspects in patients with anorexia nervosa during inpatient treatment - Buckert, Magdalena; Stroe-Kunold, Esther; Wesche, Daniela; Hellwig-Walter, Christiane; Kopf, Stefan; Simon, Joe J.; Herzog, Wolfgang; Wild, Beate (PLOS ONE, 2017)
Objective The protein hormone adiponectin promotes metabolic and psychological health. The aim of the study was to track changes in adiponectin levels in response to weight gain and to assess associations between adiponectin and psychological aspects in patients with anorexia nervosa (AN). Methods To investigate if adiponectin levels depend on AN severity, data were assessed from 11 inpatients with a very low body mass index (BMI) and a high chronicity (high severity group; HSS), and nine with less severe symptoms (LSS). During the course of treatment, serum adiponectin concentrations were assessed on a weekly basis along with BMI. Psychological variables (i.e., depression, anxiety, stress, and AN-specific symptoms) were obtained by means of electronic diaries. Longitudinal regressions and correlations were calculated to evaluate the temporal course of adiponectin and its relationship with psychological self-ratings. Results At the beginning adiponectin was not increased in HSS patients (p = .56), and only marginally elevated in LSS patients (p = 0.07) compared with controls. In HSS patients, adiponectin increased along with BMI during the first treatment phase (i.e., when the BMI of patients was below 16 kg/m2) and thereafter decreased with further weight gain. In LSS patients, adiponectin was not associated with BMI increase. Furthermore, adiponectin was strongly negatively correlated with psychological self-ratings when the BMI of patients was above 16 kg/m2, i.e., higher levels of adiponectin were related to lower ratings of depression, anxiety, and AN-specific symptoms. Discussion The study connects previous varying results by indicating that the course of adiponectin is dependent on BMI and symptom severity. Similarly, associations of adiponectin and psychological health depended on BMI.
Gesehen am 15.06.2018